1987
DOI: 10.1083/jcb.104.5.1157
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore complex glycoproteins contain cytoplasmically disposed O-linked N-acetylglucosamine.

Abstract: Abstract. A novel form of protein-saccharide linkage consisting of single N-acetylglucosamine (GIcNAc) residues attached in O-linkages directly to the polypeptide backbone has been described (Holt, G. D., and G. W. Hart, 1986, J. Biol. Chem., 261:8049-8057). This modification was found on proteins distributed throughout the cell, although proteins bearing O-linked GIcNAc moieties were particularly abundant in the cytosolic and nuclear envelope fractions of rat liver. In the accompanying article (Snow, C. M., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
258
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(272 citation statements)
references
References 20 publications
11
258
0
1
Order By: Relevance
“…Recently, Rexach et al (52) developed a method to quantify the extent of O-GlcNAc modification of proteins using a resolvable polyethylene glycol mass tag. Their results demonstrated that Nup62 from adult rat brain is heavily O-GlcNAcylated, yielding a range of O-GlcNAc-modified species, an observation that is consistent with previous findings showing that Nup62 is heavily modified in cells (53). The results of the hOGT and hOGA kinetics also enable us to estimate the relative O-GlcNAc levels expected on different protein substrates at fixed concentrations of UDP-GlcNAc and both of the enzymes, assuming that no other factors are operative.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, Rexach et al (52) developed a method to quantify the extent of O-GlcNAc modification of proteins using a resolvable polyethylene glycol mass tag. Their results demonstrated that Nup62 from adult rat brain is heavily O-GlcNAcylated, yielding a range of O-GlcNAc-modified species, an observation that is consistent with previous findings showing that Nup62 is heavily modified in cells (53). The results of the hOGT and hOGA kinetics also enable us to estimate the relative O-GlcNAc levels expected on different protein substrates at fixed concentrations of UDP-GlcNAc and both of the enzymes, assuming that no other factors are operative.…”
Section: Discussionsupporting
confidence: 70%
“…Especially noteworthy is that each Nup62 molecule, between the fingertip and N-terminal FG repeats, displays a heavily glycosylated region, each of which contains 10 single GlcNAc residues, linked to a Ser (Thr) residue (17,18). The physiological significance of what we termed the "glyco-belt" region ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we purified the labeled azidoglycoproteins via sequential anti-FLAG and immobilized metal affinity chromatographic steps and identified the captured proteins by two-dimensional liquid chromatography and tandem mass spectrometry. Importantly, numerous reported O-GlcNAcylated proteins were specifically enriched in the Ac 4 GalNAz-treated cells and absent from samples from vehicle-treated cells, including several components of the nuclear pore complex (known to be heavily glycosylated) (27,28), a Sec24 family member (29), glyceraldehyde-3-phosphate dehydrogenase (30), host cell factor C1 (31, 32), Elf-1 (33), and OGT itself (34,35) (Figs. S5B and S6).…”
Section: A Pilot Proteomics Experiments Demonstrates the Utility Of Acmentioning
confidence: 99%